Waste activated sludge pretreatment by Fe(II)-activated peroxymonosulfate oxidation under mild temperature - Liu, Changgeng; Wu, Bin; Chen, Xiao’e; Xie, Sicai (Chemical papers, 2017)
The potential of Fe(II)-activated peroxymonosulfate (Fe(II)-PMS) oxidation under mild temperature applied to pretreat waste activated sludge (WAS) was investigated in this work. The reciprocal ratio of capillary suction time to its initial value (CST 0 /CST) was used to characterize sludge dewaterability. The optimal conditions were Fe(II) 0.6 mmol g −1 VSS, PMS 1.0 mmol g −1 VSS, and temperature 60 °C, under which a high value of CST 0 /CST was obtained to be 14.0 with a CST reduction rate of 92.9%. The enhancement of sludge dewaterability was mainly contributed from the remarkable increase of the negative zeta potential and the significant decrease of extracellular polymeric substances (EPS) (especially for protein). It was further observed that Fe(II)-PMS oxidation under mild temperature was beneficial to sludge disintegration in terms of VSS reduction and the concentrations of total organic carbon (TOC) and total nitrogen (TN) in the supernatant after treatment. Therefore, Fe(II)-PMS oxidation under mild temperature is a feasible and efficient alternative technology for sludge pretreatment.